Impacting the home environment toward the prevention of childhood obesity - Rosenkranz, Richard R. (Kansas State University, 2008)
The environment can be broadly defined as all things external to an individual. One of the most important environments for children is the home in which they live, particularly with regard to the role that parents play to provide opportunities for healthful development, including adequate physical activity and healthful eating habits. Parents are the gatekeepers of children's healthful opportunities, and are influential in numerous aspects related to obesity. The present paper consists of four chapters related to impacting the home environment for prevention of obesity in children. Although obesity is a complex issue, its cause is energy imbalance, wherein less energy is expended than is consumed. Consideration of both sides of the equation is essential for obesity prevention. In this dissertation, chapter 1 serves as a literature review for the home food environment. A conceptual model is presented as an attempt to place relevant literature in the greater context of environmental variables related to childhood obesity. Frequent family meals have been shown to be protective for child and adolescent obesity, and to promote fruit and vegetable consumption. However, time pressures and lack of cooking skills are potential barriers to this healthful practice. Decreases in television viewing and sugar-sweetened beverage consumption are other home environmental aspects showing promise in the obesity prevention literature. Chapters two and three address the influence of parents on children's obesity-preventive behaviors and relative weight status. These chapters help to inform the planning of interventions to prevent obesity in children. Parent-child shared physical activity may hold promise as a strategy to decrease the likelihood of children becoming obese, and bonding may be an important consideration in programs aimed at obesity treatment or prevention. Chapter four describes the evaluation of an intervention developed to impact the home environment of young girl scouts. This intervention was implemented by troop leaders altering troop-meeting environments toward more healthful opportunities for physical activity and nutrition, and through the delivery of a scouts-tailored curriculum. Results of the intervention showed marked changes to troop meeting environments, but apparently little impact on parents or the home environment.
Keywords: Obesity; Prevention; Environment; Girl scouts; Physical activity; Nutrition; Health Sciences, Human Development (0758); Health Sciences, Nutrition (0570); Health Sciences, Public Health (0573); Psychology, Behavioral (0384)